Building Polite Character In Orphanage Children Through Fairy Tales And Short Songs - Dony Novaliendry; Elsi Permata Sari; Alisyia Guspita; Febby Elvia; Deschika Dwi Alyanti; Hafiz Anugrah; Viola Syahdriati Putri; Zahwa Rahayu (Jurnal Pengabdian Masyarakat, 2026)
Purpose: This community service activity aimed to instill the four magic words—please, sorry, excuse me, and thank you—in orphanage children through creative storytelling and songs, addressing limited guidance on politeness in institutional care settings. Method: Using qualitative action research, the study employed fairy tales, sing-along techniques, role-play simulations, and interactive discussions with 15 children aged 6–16 at Nurul Iman Enam Berlian Orphanage over three days. Practical Applications: The creative approach offers an effective, enjoyable strategy for character education that orphanages, schools, and community programs can adopt to foster polite social interactions among children. Conclusion: Results demonstrated improved understanding and application of politeness values, confirming that narrative and musical methods effectively support early character development, though sustained reinforcement and caregiver involvement remain essential for lasting behavioral change.